(untitled) (Swiss Medical Weekly, 2012)
BACKGROUND AND AIM: Hepatocellular carcinoma (HCC) is the most frequent form of primary liver cancer and chronic infection with hepatitis C virus is one of the main risk factors for HCC. This study analyses the characteristics of the patients with chronic hepatitis C participating in the Swiss Hepatitis C Cohort Study who developed HCC. METHODS: Analysis of the database of the Swiss Hepatitis C Cohort Study, a multicentre study that is being carried out in eight major Swiss hospitals since the year 2000. Patients with chronic hepatitis C and HCC were regrouped and compared to the patients without HCC. RESULTS: Among the 3,390 patients of the cohort, 130 developed an HCC. Age was one of the determining factors. Cirrhosis and its complications ascites and porto-systemic encephalopathy were associated with HCC. Males presented a higher risk for HCC than females. Alcohol consumption was associated with HCC. Diabetes mellitus was an important risk factor, especially in patients with low fibrosis. Patients with Hepatitis C genotype 2 had significantly less HCC than patients with other genotypes. A low socioeconomic status (income, education, profession) was associated with HCC. CONCLUSIONS: Beside the expected characteristics (age, gender, cirrhosis, alcohol), these data stress the role of diabetes mellitus and reveal the importance of low socioeconomic status as a risk factor for HCC in Swiss patients infected with hepatitis C virus. This vulnerable population should be closely monitored.